Preventive medicine in Quran and modern science: An applied study on the level of understanding among the staff in the halal products Research Institute at The University Putra Malaysia / Mudher Ali Hussein - Mudher , Ali Hussein (2019)
This study is entitled "Preventive Medicine in Quran and Modern Science: An Applied Study on the Level of Understanding among the Staff in the Halal Products Research Institute at the University Putra Malaysia". The significance of study lies in the fact that it deals with preventive medicine from Qur’anic perspective. The Quran shows a great concern about this issue that prohibits a number of drinks and eatables due to the pathological threats they pose to individuals and societies. Such consumables comprise a significant part of the exegetic literature on the Quran as being harmful to the human body. This is a fact that is confirmed by modern medicine. The problem of study lies in the fact that the Qur’anic instructions regarding consumption issues, one of which is the stipulation of a particular lawful method of slaughtering, are either misunderstood or completely unrealised. The study aims at highlighting the concept of preventive medicine and its objectives, and conducts a comparison between what is pinpointed in Surat Al-Ma’idah and the discoveries of modern science in preventive medicine. Moreover, the study measures how well the sample population are aware of the concept of preventive medicine, its objectives and how well it agrees with instructions of the surah in question. In addition, in order to optimally serve the purpose of study, the inductive analytical approach has been adopted, and the study culminates with a survey for pinpoint characterisation. The study is concluded with a number of findings, the most important of which are as follows: The personnel working in the stated institution (i.e., the Halal Products Research institute) have poor understanding of the concept and objectives of preventive medicine in the noble Quran. The staff in the institution under discussion has medium understanding of the scientific preventive medicine in relation to the injunctions of the surah. There are statistically significant differences amounting to (0.05≥α) between the average grades of the sample population in their agreement on the scientific meanings of the preventive medicine referred to in the Quran under the subheadings: the concept of the preventive medicine in the noble Quran, objectives of preventive medicine, scientific preventive medicine and its consistency with the injunctions of Suratul-Ma’idah. This can be attributed to the qualification variable. The study affirms that there is no relation attributable to variables of the experience years, gender and specialisation.